Bronchopulmonary dysplasia: preventive measures and therapeutic approach until discharge from the neonatal unit - Gustavo Rocha (Publicaciones Permanyer, 2024)
Bronchopulmonary dysplasia (BPD) is the most common long-term respiratory morbidity affecting very preterm infants and has a negative impact on future lung function and quality of life. BPD management during a neonatal intensive care unit (NICU) stay is mainly based on a set of preventive measures. Despite improvements in pharmacological and non-pharmacological research, only a few therapeutic measures available are supported by high-quality evidence. This review essentially focuses on preventive and therapeutic options for preterm neonates at risk of, or with established, BPD, during their NICU stay.